Candidate Psychotropics against SARS – CoV – 2: A Narrative Review - Khosravi, Mohsen (Pharmacopsychiatry, 2021)
Since few therapeutic options are clinically accessible for coronavirus disease 2019 (COVID-19), effective, safe, and globally available pharmaceuticals need to be urgently developed to prevent severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) and alleviate the severity of COVID-19. In this regard, the present paper is intended to provide an extensive review of the clinical and preclinical evidence on the psychotropics’ anti-SARS-CoV-2 effects, giving an insight into their potential applications for patients with a proven or high likelihood of COVID-19 pneumonia. The results showed that psychotropic drugs such as melatonin, lithium carbonate, valproate, olanzapine, quetiapine, clozapine, fluoxetine, escitalopram, fluvoxamine, and cannabidiol could help lower the mortality due to SARS-CoV-2 infection. According to these medications’ direct immunomodulatory actions against the destructive cytokine storm, as well as other direct/indirect mechanisms (e. g., the endolysosomal pathway modulation, interactions with specific receptors, and membrane fusion), it was perceived that such drugs could effectively weaken the worsened immune response and avoid adult respiratory distress syndrome and acute lung injury. According to the author’s analysis of the currently available evidence, there is significant support for psychotropics as complementary interventions during SARS-CoV-2 infection. However, further studies need to be carried out to assess the effects of the above psychotropic drugs in vitro and clinical settings.
Keywords: psychotropic; review; SARS-CoV-2